2020
DOI: 10.1371/journal.pone.0233683
|View full text |Cite
|
Sign up to set email alerts
|

Precarious employment and self-reported experiences of unwanted sexual attention and sexual harassment at work. An analysis of the European Working Conditions Survey

Abstract: Unwanted sexual attention (UWSA) and sexual harassment (SH) are prevalent experiences for women in working life and often accompanied by poor health. Despite increasing numbers especially of young people working in insecure and irregular employment settings, there is little empirical evidence if such precarious arrangements are associated with UWSA or SH. To investigate this, we used a representative sample of the European working population consisting of 63,966 employees in 33 countries who participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 66 publications
3
39
2
1
Order By: Relevance
“…For instance, studies have suggested power imbalance (i.e., power imbalance predisposes female staff to sexual coercion) in the workplace context, the offer of bonuses and promotion in return for sexual attention are prevalent in many workplaces including the academia [ 47 ]. Our findings corroborate prior research showing that sexual harassment of women is prevalent in diverse workplaces, including academia [ 48 , 49 , 52 , 79 , 84 ]. The finding is an urgent call for well-functioning support structures for SH's victims, and active organizational structures are also essential for preventing SH in higher education.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, studies have suggested power imbalance (i.e., power imbalance predisposes female staff to sexual coercion) in the workplace context, the offer of bonuses and promotion in return for sexual attention are prevalent in many workplaces including the academia [ 47 ]. Our findings corroborate prior research showing that sexual harassment of women is prevalent in diverse workplaces, including academia [ 48 , 49 , 52 , 79 , 84 ]. The finding is an urgent call for well-functioning support structures for SH's victims, and active organizational structures are also essential for preventing SH in higher education.…”
Section: Discussionsupporting
confidence: 91%
“…Also, WSH is a form of workplace harassment typically characterized by gender or sex lines [46]. Besides, the literature suggests that women are more likely than men to experience sexual harassment in a lifetime [47][48][49]. Fitzgerald identified three dimensions of SH.…”
Section: Introductionmentioning
confidence: 99%
“…We first restricted our analyses to 11 052 individuals who participated in at least two waves between 1988 (aged 23–31 years) and 2016 (aged 51–59 years). Then, to align with prior literature, we restricted to 10 281 individuals who were employed at least once ( 13 , 16 , 17 , 20 , 24 , 25 , 28 ). We further excluded individuals who had <40% of the survey items observed across their employed years combined (N=1730); this exclusion included self-employed individuals, who lacked data on many PE indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Third, precariously employed individuals may have limited control over both their professional and personal lives, leading to psychosocial stress. Importantly, poor employment quality may be contributing to widening health inequities, as women, people with lower education levels, and those from racialized groups tend to have a higher prevalence of PE (8,13,15,17,(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…However, these more “objective” meanings of precarity often tended to overlook the subjective, affective experience of insecurity which has instead a remarkable impact on employees, as shown by the psychological literature reviewed in the previous section [ 1 , 30 ]. Indeed, subjective job insecurity is certainly connected to work precarity, as occupational precarity entails nonstandard or atypical employment forms generally associated with a lack of security, regularity and stability, statutory rights, material rewards, working-time arrangements, training programs, protection against poverty and the like [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%